ANALISA PENDAPATAN RUMAH TANGGA NELAYAN PANCING DI KAWASAN BONE PESISIR, BONE BOLANGO - Asruddin, Asruddin (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2018)
This study aims to determine the magnitude of household income fishing line. This research was conducted in Bone Pesisir area, Bone Bolango Regency from August to December 2017. The research type used was survey with 32 fisherman household samples as respondents selected by simple random sampling technique by used questionnaire as to collect data. The data were analyzed by calculating the income of fisherman, husbandâs side income and wife income. The results showed that the average income of fishermen was Rp 2.930.881, - / month, the average husbandâs side income was Rp 837.500, - / month, the average income of wife was Rp 585.625, - / month and the average income of fishermans fishing households is Rp 4.354.006, - / month